Overcoming limitation in DFM using layer manufacturing - Ahmad, M.A.R. (Trans Tech Publications Ltd, 2014)
Design and fabrication of an object with parts embedded internally within the part has always been a difficult challenge to fabricate. This is mainly due to limitations in design for manufacturing (DFM). The objective of this work is to investigate improvements in overcoming limitations in DFM of non-metallic object with embedded part within a part through 3D printing technology and silicone rubber. 3D printing technology is a type of Rapid Prototyping (RP) method which has limitations in its material durability and product failure rate. This technology combined with silicone rubber is envisaged capable to overcome some of the limitations in DFM while increasing its durability. Layer manufacturing using 3D printing is used to construct scaffolding of the end product and silicone rubber used as material to fill the cavities. The end product is a unique âone-pieceâ outdoor water-feature cage that has no assembly of parts between its various internal and external components which entraps a free rotating ball feature inside the cage. Both limitations in DFM of a part within a part and improving prototype materials durability had been overcome. Â© (2014) Trans Tech Publications, Switzerland.